Faktor-faktor yang memengaruhi purchase intention produk bone conduction headset “Brand Shokz” di Jakarta - Wahyuni, Tri; Firdausy, Carunia Mulya (Universitas Tarumanagara, 2025)
This study aims to examine the influence of brand image, brand awareness, and perceived quality on purchase intentions of the bone conduction headset product “Shokz Brand” in Jakarta. The underlying theory applied was based on the Stimulus, Organism, and Response (SOR) Theory. The sampling method applied in this study was non-probability sampling with a purposive sampling technique. The respondent consisted of 235 buyers of bone conduction headset Shokz Brand in Jakarta. Methods to analyse data was by applying PLS-SEM. The result indicates that brand image does not have a significant effect on purchase intention. Furthermore, brand awareness and perceived quality significantly influence purchase intentions. A coefficient of determination value of R² = 0.755 indicates that 75.5% of the variance in purchase intention can be explained by the model. Therefore, PT XYZ as the official distributor of Shokz Brand needs to improve brand awareness and perceived quality to stimulate the consumers to have intention to purchase its product. Penelitian ini bertujuan untuk menguji pengaruh brand image, brand awareness, dan perceived quality terhadap purchase intention produk bone conduction headset “Brand Shokz” di Jakarta. Teori dasar yang diterapkan didasarkan pada Teori Stimulus, Organisme, dan Respon (SOR). Metode pengambilan sampel yang digunakan dalam penelitian ini adalah non-probability sampling dengan teknik purposive sampling. Responden terdiri dari 235 pembeli produk bone conduction headset Brand Shokz di Jakarta. Metode analisis data menggunakan PLS-SEM. Hasil penelitian menunjukkan bahwa brand image tidak berpengaruh signifikan terhadap purchase intention. Selanjutnya, brand awareness dan perceived quality berpengaruh signifikan terhadap purchase intention. Nilai koefisien determinasi sebesar R² = 0,755 mengindikasikan bahwa model dapat menjelaskan 75,5% variabel purchase intention. Oleh karena itu, PT XYZ sebagai distributor resmi Brand Shokz perlu meningkatkan brand awareness dan perceived quality untuk merangsang konsumen agar memiliki niat membeli produknya.